Psychiatric nursing in crisis: Lived experiences and coping strategies during the COVID-19 pandemic in the Philippines - Tamon, Alfred S.; Trajera, Sheilla M.; Lachica, Toni-An B.; Ching, Gregory S. (Edelweiss Applied Science and Technology, 2025)
Psychiatric nurses play a critical role in managing patients with maladaptive behavioral patterns, yet the COVID-19 pandemic significantly intensified their professional and personal struggles. They faced an increased workload, heightened infection risks, and emotional exhaustion, compounded by uncertainty, fear of transmitting the virus to their families, and difficulties adapting to the 'new normal.' Despite these obstacles, nurses remained committed to their work, relying on institutional protocols, personal resilience, and emotional support from family and peers to sustain their well-being. This study explores the lived experiences of psychiatric nurses in the Philippines during the COVID-19 pandemic using a qualitative phenomenological approach. Six psychiatric nurses working in a designated psychiatric facility in Bacolod City, Philippines, participated in one-on-one Zoom interviews, with data analyzed through thematic analysis. The findings reveal two key themes: (1) the challenges of working in a psychiatric hospital during the pandemic, including increased workload, fear of infection, and difficulties with PPE; and (2) surviving COVID-19 as frontline mental health workers, highlighting resilience, adaptive coping strategies, and a strong sense of professional commitment. Guided by Lazarus and Folkman’s (1984) Transactional Model of Stress and Coping, this study highlights how psychiatric nurses navigated the crisis through problem-focused and emotion-focused coping mechanisms. The findings emphasize the psychological toll of the pandemic on psychiatric nurses and underscore the need for institutional mental health interventions, workplace support systems, and improved crisis preparedness to safeguard their well-being in future public health emergencies.